Nanotechnology in Industrial Wastewater Treatment - Roy, Arup (IWA Publishing, 2015)
Nanotechnology in Industrial Wastewater Treatment is a state of the art reference book. The book is particularly useful for wastewater technology development laboratories and organizations. All professional and academic areas connected with environmental engineering, nanotechnology based wastewater treatment and related product design are incorporated and provide an essential resource. The book describes the application and synthesis of Ca-based and magnetic nano-materials and their potential application for removal/treatment of heavy metals from wastewater.